DETERMINANTS OF THE NON-PERFORMING LOAN RATIO IN THE BANKING SECTORS OF CENTRAL AND EASTERN EUROPE COUNTRIES - K. Kil; R. Ciukaj; O. Druhov; N. Gritsenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
In the last decade, the quality of loan portfolios has deteriorated significantly in most countries around the world. This is result of the financial crisis, that hit the global economy in 2007—2009. Since then, the average quality level of bank assets has deteriorated rapidly due to the global economic recession. The fact, that the quality of credit exposures is closely related to the economic cycle is well known and is not surprising. However, the deterioration in the quality of loan exposures varied widely from country to country. In the article authors attempt to analyze the panel data to assess the impact of different factors on the NPL level in the banks of Central and Eastern European countries that are members of the EU. The literature indicates two basic sets of factors influencing changes in the level of non-performing loans. The first group concerns external factors, which include general macroeconomic conditions that may have a potential impact on borrowers’ ability to repay loans. The second group includes  bank’s specific factors (resulting from the functioning of banks), which, according to the results of previous analyzes, have a smaller impact on the volatility of non-performing loans. Using dynamic and static panel-based approach, authors examine the determinants of the loan portfolios with impairment of 138 banks  in the entire available period between 2008 and 2017. The results show that the NPLs of banks operating in Central and Eastern Europe countries can be explained mainly by significant macroeconomic factors, such as GDP and the unemployment rate, as well as bank-specific factors such as ROA, interest margin or bank size measured by the value of assets. The results constitute a significant contribution to the discussion on the possibility of solving the problem of a significant increase in the value of impaired loans in the post-crisis period.